Physiological demands of elite cross-country skiing during a real competition - Gonzalez-Millan, C.; Perez-Brunicardi, D.; Salinero, J. J.; Lara, B.; Abian-Vicen, J.; Areces, F.; Ruiz-Vicente, D.; Soriano, L.; Del Coso, J. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to assess different physiological variables before and after a 5-km (women) and 10-km (men) cross-country skiing competition to determine potential mechanisms of fatigue. Fourteen elite-level skiers competed in an official cross-country skiing competition using the classical style (9 men and 5 women). Instantaneous skiing velocity was measured during the race by means of 15-Hz global positioning system devices. Before and after the race, a sample of venous blood was obtained to assess changes in blood lactate and serum electrolyte and myoglobin concentrations. Prerace to postrace changes in blood oxygen saturation, forced vital capacity during a spirometry test, jump height during a countermovement jump, and handgrip force were also measured. Mean race speed was 15.8 ± 2.5 and 15.4 ± 1.5 km/h, whereas mean heart rate was 171 ± 6 and 177 ± 3 b/min for men and women, respectively. There were no significant prerace to postrace changes in jump height, handgrip force, and forced vital capacity in men and women. Blood oxygen saturation was reduced from prerace to postrace in men (95.9 ± 2.1% to 93.1 ± 2.3%, p = 0.02) and women (97.8 ± 1.1% to 92.4 ± 2.1%, p < 0.01), whereas blood lactate concentration increased at the end of the race in men (1.4 ± 0.5 to 4.9 ± 2.1 mmol/L, p < 0.01) and women (1.9 ± 0.1 to 6.9 ± 3.2 mmol/L, p < 0.01). After the race, blood markers of muscle damage were at low concentrations, whereas serum electrolytes remained unchanged. Fatigue in 5- and 10-km cross-country skiing competitions was related to a reduced blood oxygen carrying capacity and presumably increased muscle and blood acidosis, whereas the influence of exercise-induced muscle damage on fatigue was minor.